Support For Cigarette Tax In Tobacco-Producing States (Tufts Archival Research Center, 2007)
Chart comparing responses to questions about cigarette tax increases between voters from North Carolina, Kentucky, South Carolina, Virginia, Georgia and Tennessee (Tobacco-state voters). Shows a consistent ratio of 65% of tobacco-state voters for increasing cigarette tax to 35% against.